استخدام الإنفوجرافيك التعليمي المتحرك كمنظم متقدم في تدريس الأحياء لتنمية مهارات التفكير الشكلي وخفض العبء المعرفي لدى طالبات المرحلة الثانوية ذوات السعة العقلية المختلفة - تمساح، ابتسام على أحمد إبراهيم Temsah, Ibtesam Ali Ahmed Ibrahim (جامعة الوادي الجديد - كلية التربية, 2022)
هدف البحث إلى: تعرف أثر استخدام الإنفوجرافيك التعليمي المتحرك كمنظم متقدم في تدريس الأحياء لتنمية مهارات التفكير الشكلي وخفض العبء المعرفي لدى طالبات المرحلة الثانوية ذوات السعة العقلية المختلفة، ولتحقيق هذا الهدف تم اختيار الباب الرابع من كتاب الأحياء للصف الأول الثانوي، وتكونت عينة البحث من (67 طالبة) يمثلون مجموعتي البحث (التجريبية والضابطة)، وتضمنت مواد وأدوات البحث من (1) اختبار السعة العقلية، (2) دليل المعلم لتدريس الباب الرابع "تصنيف الكائنات الحية" باستخدام الإنفوجرافيك التعليمي كمنظمات متقدمة، (3) اختبار مهارات التفكير الشكلي، (4) اختبار العبء المعرفي، تم تطبيق أدوات البحث قبليا على طالبات مجموعتي البحث ثم تدريس الباب الرابع "تصنيف الكائنات الحية" باستخدام الإنفوجرافيك التعليمي المتحرك كمنظم متقدم للمجموعة التجريبية، وتدريس الباب كما هو وارد في كتاب المدرسة للمجموعة الضابطة، تم تطبيق أدوات البحث بعديا على طالبات مجموعتي البحث، واستخدمت الأساليب الإحصائية المناسبة لحساب الفروق في متوسطات الدرجات لكل من المجموعة التجريبية والمجموعة الضابطة، كذلك الفروق بين متوسطات درجات طالبات المجوعة التجريبية ذوي السعة العقلية المختلفة، وأظهرت نتائج البحث عن وجود فروق ذات دلالة إحصائية بين متوسطات درجات طالبات المجموعة التجريبية، ودرجات طالبات المجموعة الضابطة في التطبيق البعدي في اختبار مهارات التفكير الشكلي واختبار العبء المعرفي لصالح المجموعة التجريبية، وعدم وجود فروق ذات دلالة إحصائية بين متوسطات درجات طالبات المجموعة التجريبية يرجع إلى السعة العقلية لديهن بعد تطبيق التجربة. The research aimed to investigate the effect of using educational animated infographic as an advanced organizer in teaching biology to develop formal thinking skills and reduce the cognitive load among secondary school students with different mental capacity. To achieve this goal, the fourth chapter of the biology textbook for the first secondary grade was selected, and the research sample consisted of (67 students) representing the two research groups (experimental and control). The instruments included (1) mental capacity test, (2) teacher's guide for teaching chapter four " classification of living organisms" reformulated using educational animated infographics, (3) formal thinking skills test, (4) cognitive load test. The research tools were applied before, then teaching the fourth chapter “classification of living organisms” using the educational animated infographic as an advanced organizer for the experimental group, and teaching the chapter as contained in the school textbook for the control group, the research tools were applied again to the students of the two research groups, and appropriate statistical methods were used to calculate the differences in the mean scores for each of the experimental group and the control group, Likewise, the differences between the mean scores of students of the experimental group students with different mental capacity, and the results of the research showed that there are statistically significant differences between the mean scores of the experimental group students and the scores of the control group students in the post application in testing the formal thinking skills and the cognitive load in favor of the experimental group, and there are no statistically significant differences between the mean scores of the experimental group students due to their mental capacity after applying the experiment.
Keywords: تكنولوجيا التعليم -- الإنفوجرافيك المتحرك -- مادة الأحياء -- مهارات التفكير -- طلبة المرحلة الثانوية